Molecular cloning of cellular genes encoding retinoblastoma-associated proteins: identification of a gene with properties of the transcription factor E2F. - Shan, B (1992)
The retinoblastoma protein interacts with a number of cellular proteins to form complexes which are probably crucial for its normal physiological function. To identify these proteins, we isolated nine distinct clones by direct screening of cDNA expression libraries using purified RB protein as a probe. One of these clones, Ap12, is expressed predominantly at the G1-S boundary and in the S phase of the cell cycle. The nucleotide sequence of Ap12 has features characteristic of transcription factors. The C-terminal region binds to unphosphorylated RB in regions similar to those to which T antigen binds and contains a transactivation domain. A region containing a potential leucine zipper flanked by basic residues is able to bind an E2F recognition sequence specifically. Expression of Ap12 in mammalian cells significantly enhances E2F-dependent transcriptional activity. These results suggest that Ap12 encodes a protein with properties known to be characteristic of transcription factor E2F.